One-dimensional CdS nanowires–CeO2 nanoparticles composites with boosted photocatalytic activity1. (24th September 2015) - Zhang, Xin; Zhang, Nan; Xu, Yi-Jun; Tang, Zi-Rong
<x xml:space="preserve">Abstract</x> The one-dimensional CdS nanowires–CeO2 nanoparticles composites exhibit enhanced visible-light-driven photoactivity toward selective reduction of nitroaromatics and water splitting to hydrogen.